Гірсько-горбкуватий ландшафтний район дендропарку Тростянець: історія формування, прийоми композиції - Ilyenko, A.A.; Medvedev, V.A. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2010)
The historical data of the creation of the artificial mountain undulating land in the dendrological park Trostyanets and the methods of its composition are given.